Flucytosine‐based prodrug activation by cold physical plasma. Issue 9 (27th May 2022) - Ahmadi, Mohsen; Potlitz, Felix; Link, Andreas; von Woedtke, Thomas; Nasri, Zahra; Wende, Kristian
Abstract: Reactive oxygen species (ROS) are known to trigger drug release from arylboronate‐containing ROS‐responsive prodrugs. In cancer cells, elevated levels of ROS can be exploited for the selective activation of prodrugs via Baeyer–Villiger type oxidation rearrangement sequences. Here, we report a proof of concept to demonstrate that these cascades can as well be initiated by cold physical plasma (CPP). An analog of a recently reported fluorouracil prodrug based on the less toxic drug 5‐fluorocytosine (5‐FC) was synthesized with a view to laboratory safety reasons and used as a model compound to prove our hypothesis that CPP is suitable as a trigger for the prodrug activation. Although the envisioned oxidation and rearrangement with successive loss of boronic acid species could be achieved by plasma treatment, the anticipated spontaneous liberation of 5‐FC was inefficient in the model case. However, the obtained results suggest that custom‐tailored CPP‐responsive prodrugs might become an evolving research field. Abstract : This study reports a proof of concept to demonstrate the activation of reactive species‐responsive prodrugs by cold physical plasma (CPP). CPP could achieve the envisioned oxidation and rearrangement with the loss of boronic acid, but the anticipated spontaneous liberation of 5‐fluorocytosine was inefficient in the studied model. Still, the obtained results suggest that custom‐tailored CPP‐responsive prodrugs might become an evolving research field.